Antitumor effects of vitamin B12 in vitro, in vivo, in silico - O. A. Gromova; D. E. Frolova; I. Yu. Torshin; M. V. Filimonova; M. A. Sorokina; I. A. Reyer; O. A. Limanova; L. E. Fedotova; L. A. Maiorova (IRBIS LLC, 2023)
Objective: to investigate the antitumor effects of various forms of vitamin B12 in combination with various synergistic vitamins and evaluate the prospects for clinical applications.Material and methods. Cell lines BT-474 (breast ductal carcinoma) and A549 (lung carcinoma) were used as an in vitro cell model, and transplantable epidermoid Lewis lung carcinoma (LLC) was used as an in vivo animal tumor model. Animal studies of LLC were carried out on 25 male F1 hybrid mice (age 2.5-3 months, body weight 23-26 g). In silico research was conducted as a systematic computer analysis of 9,326 scientific sources.Results. In vitro studies on cultures of two human tumor cell lines (BT-474 and A549) confirmed the cytotoxic effect of vitamin B12 (aquacobalamin). It has been shown that vitamin B12 has weak cytotoxic properties in the concentration range of 3.125-200 μg/L (IC50>200 nM), and its hydrophobic derivative (heptamethyl cyanoquacobyric acid ester) significantly reduces the survival of tumor lines. BT-474 and A549 cells at high concentrations (100-200 µg/l, IC50~100 nM). Experimental animals with an in vivo LLС model easily tolerated a drug based on vitamin B12. Exposure to the drug up to the 21st day of LLС development was accompanied by an increasing tendency to inhibit tumor growth by 10-20% (р=0.059). The results of a systematic in silico review of the literature show that clinical data confirmed the significant antitumor effect of vitamin B12.Conclusion. The cellular model indicated the antitumor properties of vitamin B12 and its hydrophobic derivative. With subchronic intragastric administration of B12 to tumor-bearing animals, a steady tendency to inhibit the LLС growth was observed. Analysis of clinical data confirmed the feasibility of the antitumor use of vitamin B12 individually and in combination with synergistic vitamins.